Respuesta :
Answer:
y = -x+3
Step-by-step explanation:
First find the slope
m = ( y2-y1)/(x2-x1)
= ( 2 - -3)/( 1 - 6)
( 2+3)/( 1-6)
5/ -5
-1
The slope is -1
We can use slope intercept form
y = mx+b where m is the slope and b is the y intercept
y = -x+b
Substitute a point into the equation
2 = -1 +b
Add 1 to each side
2+1 = -1+1+b
3 = b
y = -x+3
y = -x + 3
[tex]m = \frac{y_{1} - y_{2} }{x_{1} - x_{2}}[/tex]
[tex]m = \frac{6 - 1 }{-3 - 2}[/tex]
[tex]m = \frac{5 }{-5}[/tex]
[tex]m=-1[/tex]
y = mx + b
substitute
2 = -1(1) + b
2 = -1 + b
3 = b